2013
DOI: 10.1111/ijn.12049
|View full text |Cite
|
Sign up to set email alerts
|

Stress among parents of infants with neural tube defect and its associated factors

Abstract: The purpose of this study was to assess the stress among parents (either the mother or the father) of infants with neural tube defects (NTDs) and its associated factors. Using Parenting Stress Index-Short Form (PSI-SF), 100 parents of infants with NTDs were compared with 100 parents as a normative group. The total mean score for parents of infants with NTDs was 104.0 (standard deviation (SD) = 22.9) compared with 84.3 (SD = 18.9) for parents of infants without NTDs. Fifty-three (53.5%) parents of infants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It is also noteworthy that there was a negative relationship between parenting stress and estimated household income in the participants with Tourette syndrome at a trend level. Previous studies have also found that lower family income was significantly associated with increased parenting stress, both in parents of children with neural tube defects 22 and in parents of children with a variety of chronic childhood diseases (cancer, asthma, type 1 diabetes or cystic fibrosis). 23 …”
Section: Discussionmentioning
confidence: 94%
“…It is also noteworthy that there was a negative relationship between parenting stress and estimated household income in the participants with Tourette syndrome at a trend level. Previous studies have also found that lower family income was significantly associated with increased parenting stress, both in parents of children with neural tube defects 22 and in parents of children with a variety of chronic childhood diseases (cancer, asthma, type 1 diabetes or cystic fibrosis). 23 …”
Section: Discussionmentioning
confidence: 94%
“…Comparing stress, uncertainty, anxiety, and depression levels between parents of term infants and parents of preterm infants was beyond the scope of this study. Similarly, parents of infants with congenital anomalies were not included because parents who have infants with congenital anomalies and parents of infants undergoing surgeries experienced more stress than parents of healthy infants (AlAkour, Khader, & Hamlan, 2013;Fonseca, Nazaré, & Canavarro, 2012;Joseph, Mackley, Davis, Spear, & Locke, 2007). Therefore, only parents of preterm infants without physical anomalies and complex surgery were included in this study.…”
Section: Samplementioning
confidence: 99%